Effect of age on the efficacy and safety of clopidogrel plus aspirin vs aspirin alone in acute mild-to-moderate stroke: a secondary analysis of the ATAMIS trial - Yan, Hong-Ting; Cui, Yu; Li, Zi-Ang; Cai, Ji-Ru; Wang, Qi; Hou, Xiao-Wen; Chen, Hui-Sheng (Frontiers in Neurology, 2025)
ObjectivesThe association between age and the effect of antiplatelet therapy on clinical outcomes in patients with ischemic stroke remains unclear. This study aimed to explore the effect of age on the efficacy and safety of dual versus mono antiplatelet therapy in patients with mild-to-moderate ischemic stroke, based on the Antiplatelet Therapy in Acute Mild to Moderate Ischemic Stroke (ATAMIS) trial.MethodsThis secondary analysis was based on the full analysis set from the ATAMIS trial. The primary outcome was an excellent functional outcome at 90 days, which was defined as a modified Rankin Scale (mRS) score of 0–1. The treatment effect of clopidogrel plus aspirin versus aspirin alone on outcomes was analyzed using age as either a categorical variable (age <65 vs. ≥65) or a continuous variable.ResultsA total of 2,831 patients were included, with 1,249 in the subgroup aged <65 years and 1,582 in the subgroup aged ≥65 years. Compared to aspirin alone, clopidogrel plus aspirin significantly increased the likelihood of achieving an mRS score of 0–1 at 90 days in the ≥65-year age subgroup (adjusted OR, 0.77; 95% CI, 0.61–0.98; p = 0.031) but not in the <65-year age subgroup (78.02% vs. 78.62%, adjusted OR, 0.99, 95% CI, 0.75–1.32, p = 0.964). When age was analyzed as a continuous variable, the probability of an excellent functional outcome gradually decreased with advancing age in both treatment groups, but the decline was more pronounced in the aspirin-alone group, suggesting a relatively greater advantage of dual therapy among older patients.ConclusionOur findings indicate that short-term dual antiplatelet therapy is associated with improved functional outcomes in patients aged ≥65 years but not in those aged <65 years. These findings suggest that age should be considered when developing antiplatelet strategies for treating acute mild-to-moderate ischemic stroke.Clinical trial registrationClinicalTrials.gov, NCT02869009.